Impairment in the Intention Formation and Execution Phases of Prospective Memory in Parkinson's Disease - Jia, Shu-Hong; Li, Kai; Su, Wen; Li, Shu-Hua; Chen, Hai-Bo (Frontiers in Neuroscience, 2018)
Objective: Patients with Parkinson’s disease have prospective memory impairments. However, less is known about distinct phases of prospective memory in these subjects. In the present study, we aimed to examine the specific phase(s) of prospective memory that was impaired in patients with Parkinson’s disease. Methods: The study included 31 Parkinson’s disease patients and 27 healthy controls. Four phases of prospective memory (intention formation, retention, initiation, and execution) were examined in a complex prospective memory task. In this task, the participants were asked to form a sophisticated plan of performing six-subtasks to obtain the highest score, and then execute the plan following a cue embedded in a questionnaire. Global cognitive function and relevant cognitive abilities, including attention, short-term memory, working memory and inhibition, were also evaluated during the retention phase of the prospective memory task. Results: Intention formation was impaired in Parkinson’s disease patients (P<0.001 vs. healthy controls). This impairment could not be attributed to deficits in other cognitive functions. The score of intention execution was also lower in Parkinson’s disease patients (P=0.004 vs. healthy controls). Such a difference was related to working memory deficits in Parkinson’s disease. The intention retention and initiation were intact in Parkinson’s disease patients. The score of intention execution correlated negatively with disease severity and disease duration. Conclusions: Prospective memory in Parkinson’s disease patients is impaired at the phase of intention formation. The worse performance of intention execution in Parkinson’s disease may be related to working memory deficits. In addition, the prospective memory impairment might progress with increasing disease duration and severity.